(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This article analyzes the short film Aquém das Nuvens (2010), observing how the narrative and visual constructions of the characters Nenê and Geralda, an elderly black couple with positive emotional exchanges, are carried out. The study dialogues with the constructionist perspective of Applied Linguistics, Critical Race Theory and Cultural and Feminist Studies, starting from bell hooks’ thinking on representation to discuss ways of resistance and subversion to visual stereotypes, often associated with black people in cinema, composing a powerful and positive imagery field that permeates the social imaginary.